Análisis de la balanza comercial de Colombia - Estados Unidos desde la aplicación del tratado de libre comercio: maíz, durazno, manzana, aceite de oliva y aceite de maíz (2019)
In this monograph is made an analysis of the Trade Balance of Colombia and the United States of America making an emphasis on the agricultural sector of both countries, taking a historical account of the exporting and importing economy of the mentioned countries and comparing the before and after of the Trade Balance since the signing of the Free Trade Agreement, focused on the Colombian and American agricultural economy. The main analysis is based on arguing the different qualities and limitations of the Free Trade Agreement to boost or decelerate the internal economy of each country, speaking in the specific case Colombia – United States of America. The analysis was made taking into account the different factors that may affect the Trade Balances, in this particular case of study, and to conclude the level of impact that had the signing of this trade agreement in both countries and provide possible solutions to the deficiencies that Colombia may come to present that guarantees a better use of the Free Trade Agreement with the United States.